1986
DOI: 10.1111/j.1365-2141.1986.tb05545.x
|View full text |Cite
|
Sign up to set email alerts
|

Female marrow donors increase the risk of acute graft‐versus‐host disease: effect of donor age and parity and analysis of cell subpopulations in the donor marrow inoculum

Abstract: Summary. We evaluated 27 factors for their influence on acute graft‐versus‐host disease (GVHD) in 40 recipients of HLA‐identical sibling marrow transplants. These factors included the doses of mononuclear cell subpopulations present in the donor marrow inoculum quantitated using a panel of monoclonal antibodies. Female donors were associated with increased severity of acute GVHD, and the older the female donor the greater this effect. Increasing donor parity was also associated with an increased risk of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…[1][2][3][4] Older donor age has been shown to be associated with poorer outcome of CI-HSCT through a combination of higher treatment-related mortality (TRM) and relapse. [5][6][7][8] However, it is not known if donor age affects the outcome of RI-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Older donor age has been shown to be associated with poorer outcome of CI-HSCT through a combination of higher treatment-related mortality (TRM) and relapse. [5][6][7][8] However, it is not known if donor age affects the outcome of RI-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…This was unexpected since previous studies have shown that a female donor to a male recipient resulted in worse outcomes due to a higher incidence of GVHD. 27 However, female sex has been identified as a favorable risk factor for long-term survival after treatment for AML. 28 We also found that a donor graft derived from PBSCs predicted a worse outcome than a graft derived from BM.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 These responses must in general be well tolerated but HY immunization may also have harmful effects as indicated in SCT. [37][38][39][40] In late pregnancy, apoptotic syncytiotrophoblast debris is normally shed in large quantities (several grams per day) from the placenta, 41 and after being processed, peptides derived from HLA, HY and other minor HY antigens are presented to CD4 + and CD8 + T lymphocytes 42 in local lymph nodes. This presentation usually takes place under non-inflammatory conditions; resulting in T lymphocytes being tolerized against fetally derived peptides.…”
Section: Discussionmentioning
confidence: 99%